Toxins and Hemostasis 2010
DOI: 10.1007/978-90-481-9295-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venomics, Antivenomics, and Venom Phenotyping: The Ménage à Trois of Proteomic Tools Aimed at Understanding the Biodiversity of Venoms

Abstract: This review covers the application of proteomic protocols ("venomics", "antivenomics", and "venom phenotyping") to studying the composition and natural history of snake venoms, and the crossreactivity of antivenoms against homologous and heterologous venoms. Toxins from the same protein family present in venoms from snakes belonging to different genera often share antigenic determinants. This circumstance offers the possibility of defining the minimal set of venoms containing the epitopes necessary to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Hence, most snake venoms of family Viperidae (vipers and pitvipers) analyzed by state-of-the-art proteomic tecniques comprise several tens to some hundreds of molecules. 17,2026 Cerberus rynchops venom represents another very low complexity proteome. It appears to contain a total of five major proteins, one isoform each of metalloproteinase, CRISP and C-type lectin and two major isoforms of ryncolins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, most snake venoms of family Viperidae (vipers and pitvipers) analyzed by state-of-the-art proteomic tecniques comprise several tens to some hundreds of molecules. 17,2026 Cerberus rynchops venom represents another very low complexity proteome. It appears to contain a total of five major proteins, one isoform each of metalloproteinase, CRISP and C-type lectin and two major isoforms of ryncolins.…”
Section: Resultsmentioning
confidence: 99%
“…For antivenomics 17 , 1 mg of crude C. tigris venom in 300 μl of 0.2 M phosphate, pH 7.0, was incubated overnight at room temperature and with gentle stirring with 10 mg of rabbit IgG antibodies affinity-purified from the antiserum raised against a mixture of venoms from C. d. terrificus , C. simus , and C. lepidus lepidus . IgG-antigen immunocomplexes were pulled down with Agarose-Protein-A (ABT) beads capable of retaining 25 mg of IgG molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Recent proteomic studies (Table 2) have convincingly shown that snake venoms are among the most complex known animal secretions. Viperid venoms typically contain at least 30–40 different toxins representing 8–12 protein families, including Zn 2+ ‐dependent metalloproteinases, phospholipases A 2 , serine proteinases, C‐type lectin‐like proteins, cysteine‐rich secretory proteins, disintegrins, L‐amino acid oxidases, and bradykinin‐potentiating peptides (Fox & Serrano, 2008; Calvete, 2010). Elapid venoms are equivalently complex and include compounds from many of the same protein families, but they also include three‐finger toxins and other compounds that are absent or uncommon in viperid venoms (Mackessy, 2010).…”
Section: Immunity To Snake Venommentioning
confidence: 99%
“…On the other hand, this knowledge can be useful for physicians to treat the symptoms of bitten patients. It is known that, in North American Viperidae snakes, there is an inverse relationship between toxicity of the venom and the content and activity of metalloproteinases [12]. This means that different people bitten by the same snake species may exhibit different levels of exacerbation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the knowledge of precise venom composition and of ontogenetic, individual, and geographic venom variability may have a positive effect on the treatment of bite victims and in the selection of specimens for the generation of improved antidotes. Moreover, complex knowledge about venom composition, common and unique antigenic determinants, and their reactivity with antibodies may in the future lead to defining the minimal set of venoms containing all epitopes necessary to generate therapeutic broad-range polyvalent antiserum [12]. …”
Section: Introductionmentioning
confidence: 99%